The Indonesian Species of Rennellia Korth. (Rubiaceae) - SURATMAN SURATMAN (Biodiversitas Journal of Biological Diversity, 2008)
The objective of the research was to investigate the Indonesian species of Rennellia Korth. based on their morphological characters. The investigation on morphological characters was based on herbarium specimens at the Herbarium Bogoriense and Herbarium Andalas University. Additional specimens also were collected during the course of the field work. There are four species recognized, i.e., Rennellia elliptica Korth., Rennellia elongata (King & Gamble) Ridl., Rennellia morindiformis (Korth.) Ridl. and Rennellia speciosa (Wall. ex Kurz) Hook.f. An identification key to the species was produced and detailed description of the taxa was also provided. The natural history data including habitat, distribution, uses and vernacular names were also presented.Key words: Rennellia Korth., Indonesia, morphological characters